Udzielanie absolutorium członkom organów spółdzielni w świetle orzecznictwa sądowego - Wajda, Dominika (PRAWO i WIĘŹ, 2023)
Article focuses on the subject of giving dischage to the board of directors in the Cooperative. This subject is really complicated and it was rarely presented in doctrine. To make it easier to understand the article contains representative judicial decisions. The issue of discharge is undoubtedly much more popular in the filed od company law than in the fild of cooperative law. However, the judicature concernig discharge under cooperative law may be a source of interesting reflections in capital companies.